Pengaruh Perilaku Konsumtif Terhadap Remaja di Era Digital - Ulvah Aulia Putri; Tasya Ayunda; Zeni Wulandari; Eka Darliana; Anisa Noverita (Prodi Pendidikan IPS STKIP AL MAKSUM, 2026)
Consumptive behavior among adolescents in the digital era has developed into an increasingly significant problem, along with the widespread use of social media, the rapid growth of e-commerce platforms, and the ease of digital transaction systems that collectively shape the consumption patterns of the younger generation. This condition deserves serious attention because it has the potential to affect character formation, the level of independence in financial management, and the psychosocial welfare of adolescents. This study aims to examine the influence of consumptive behavior on adolescents in the digital era by focusing on three main factors, namely the intensity of social media use, the level of self-control, and financial literacy. The approach used is quantitative with an explanatory survey design. Data collection was carried out through the distribution of structured questionnaires to adolescents who actively use digital media, then analyzed using validity tests, reliability tests, and multiple linear regression techniques. The results of the study show that the intensity of social media use has a positive and significant influence on adolescents' consumptive behavior. Self-control has been shown to have a significant negative effect, indicating that the better the adolescent's ability to control themselves, the lower the tendency to consummate behavior is shown. Financial literacy has a relatively weaker influence than the other two variables